Nanoacteen: silver nanoparticles hand sanitizer lotion / Nur Maisarah Sarizan ... [et al.] - Sarizan, Nur Maisarah; Khazali, Ahmad Suhail; Ahmad Kamil, Khairunnisa (2022)
A person can become infected by touching their eyes, nose, or mouth after making contact with a contaminated surface. Therefore, keeping proper hand hygiene is crucial to avoid infections and other new health risks. There are various types of hand sanitizers available commercially, and using hand sanitizer regularly is necessary to maintain hand cleanliness. However, doing so may cause dryness or irritation to the skin. NanoActeen is a new formulation of hand sanitizer lotion that contains active ingredients named green synthesized-silver nanoparticles from snail mucin and mangosteen peel extract. It is a practical two-in-one daily moisturizer that not only hydrates dry skin but also kills bacteria when necessary. Silver nanoparticles (AgNPs) have gained much attention due to their unique properties which can be incorporated into antimicrobial applications and cosmetic products. Here, a nontoxic, eco-friendly, and cost-effective method has been established for the green synthesis of AgNPs using extracts of snail mucin (Achatina fulica) and mangosteen peel (Garcinia mangostana). These substances are claimed to have good antimicrobial properties, able in curing various diseases, slowing the aging process, and overcoming skin problems. Overall, NanoActeen has antimicrobial qualities that could kill viruses and bacteria while hydrating the skin and relieving mild skin irritation, making it an effective hand sanitizer lotion.